The Content of Placer Heavy Mineral and Characteristics of REE at Toboali Coast and Its Surrounding Area, Bangka Belitung Province - Noor CD Aryanto; Udaya Kamiludin (Marine Geological Institute of Indonesia, 2016)
Bangka Island and surrounding areas (including coast and seabed sediments) is known as main tin producer (cassiterite) in the world as these part of the Southeast Asia Granitic belt, but in fact, other than as a producer of tin, Bangka Belitung is also as heavy mineral placer (as accessories mineral) and REE potential producer which one based on the geological conditions.The potential of accessories minerals on sediment coast, other than cassiterite that occurs around Betumpak Cape, i.e: magnetite (7.86 %), ilmenite (4.9%), zircon (2.51%) and apatite (1.07%) respectively with content. While the content of monazite by using a hand drill has the potential content of up to 67.8 g/m3, while the content of monazite hypothetical resources off the coast of Bangka approximately 471,087,689 m3. As for the content of monazite hypothetical resources off the coast of South Bangka are approximately 23,995,820 m3.At Toboali coast, South Bangka the presence of REE in sediments are above the Earth's crust generally. Theyâ€™re concentrations, such as La (5.07 to 199 ppm), Ce (106-394 ppm), Pr (5.11-59.7 ppm), Nd (16.5-201 ppm), Sm (9.97-52.3 ppm), Eu (0.18-1.55 ppm), Gd (9.11-39.3 ppm), Tb (1.35-8.14 ppm), Dy (9.01-56.3 ppm), Ho (1.89-12.3 ppm), Er (5.19-33.9 ppm), Tm (0.77-5.62 ppm), Yb (3.3-37.5 ppm) and Lu (0.71-5.41 ppm). LREE (La-Eu) highest content is generally found in the location of the tailings sludge (TBL-13C), not so in HREE (Gd-Lu), the highest content is widely available on the sandy beach sediments (TBL-13B). Tectonic environment of Toboali granitoid rocks by plotting a spider diagram refers to the chondrite normalization is continental magmatic arc.Keywords: Placer heavy mineral, REE, Granitic Belt, Bangka Belitung Province.Â Pulau Bangka dan daerah sekitarnya (termasuk di pantai dan sedimen dasarlaut) telah lama dikenal sebagai penghasil timah (kasiterit) utama di dunia sebagai dari bagian Jalur Granit AsiaTenggara, selainmineral berat sebagai pembawa unsur tanah jarang (UTJ) sangat dimungkinkan mengingat kondisi geologinya.Potensi mineral ikutan di sedimen pantai selain kasiterit, seperti di pantai Muntok antara lain, seperti magnetit (7,86%), ilmenit (4,9%), zirkon (1,32%) dan apatit (1,07%). Adapun kandungan monasit berdasarkan hasil pemboran tangan memperlihatkan kandungan hingga 67,8 g/m3 dengan kandungan potensi sumber daya di seluruh Pantai Bangka sekitar 471.087.689 m3 dengan potensi sumberdaya hipotetik di Pantai Bangka Selatan mendekati 23.995.820 m3. Di Pantai Toboali, Bangka Selatan kehadiran Unsur Tanah Jarang (UTJ) dalam sedimen, umumnya di atas konsentrasi kerak bumi. Kandungan unsur tanah jarang tersebut, seperti La (5,07 - 199 ppm), Ce (106-394 ppm), Pr (5,11-59.7 ppm), Nd (16,5-201 ppm), Sm (9,97-52,3 ppm), Eu (0,18-1,55 ppm), Gd (9,11-39,3ppm), Tb (1,35-8,14 ppm), Dy (9,01-56,3 ppm), Ho (1,89-12,3 ppm), Er (5,19-33,9 ppm), Tm (0,77-5,62 ppm), Yb (3,3-37,5 ppm) dan Lu (0,71-5,41 ppm). Kandungan tertinggi unsur tanah jarang ringan (UTJ-R) seperti La hingga Eu umumnya dijumpai pada lokasi tailing (TBL-13C) berbeda halnya dengan unsur tanah jarang berat (UTJ-B), kandungan tertingginya dijumpai pada sedimen pantai pasiran (TBL-13B). Berdasarkan hasil perajahan pada diagram laba-labanya, memperlihatkan bahwa lingkungan tektonik granit Toboali merupakan busur benua magmatik. Kata kunci: Mineral berat letakan, Unsur Tanah Jarang (UTJ), Jalur Granit, Provinsi Bangka Belitung